AI-supported approach for human-building interaction implemented at furniture scale - Bier, Henriette; Hidding, Arwin; Brancart, Stijn; Luna-Navarro, Alessandra; Khademi, Seyran; van Engelenburg, Casper (Frontiers in Computer Science, 2024)
Human-Building Interaction (HBI) relies on sensor-actuator networks that are increasingly supported by Artificial Intelligence (AI). This paper presents a novel AI-supported Design-to-Robotic-Production-Assembly and -Operation (D2RPA&O) approach for reconfigurable furniture. It involves a multidisciplinary approach that relies on the integration of various domains such as architecture, robotics, computer, and material science. It contributes to the advancement of HBI by employing spatial reconfiguration relying on AI and lightweight material design, which is of relevance, particularly when the furniture consists of non-identical but similar components that are re-/ configured in a variety of possible combinations.